Application of graphene nanoplatelets and graphene magnetite for the removal of emulsified oil from produced water. Issue 2 (April 2018) - Abou Chacra, Lamis; Sabri, Muhammad Ashraf; Ibrahim, Taleb H.; Khamis, Mustafa I.; Hamdan, Nasser M.; Al-Asheh, Sameer; AlRefai, Massa; Fernandez, Carlos
Abstract: Graphene and its magnetite derivative were used as adsorbents for removal of emulsified oil from produced water. The experimental parameters for maximum emulsified oil removal efficiency and effective regeneration of these adsorbents were determined. The best parameters in terms of dosage, contact time, pH, salinity and temperature were 3.00 g/L, 60.0 min, 10.0, 1500 ppm and 25.0 °C for graphene nanoplatelets, and 4.00 g/L, 30.0 min, 3.5, 1000 ppm and 25.0 °C, for graphene magnetite, respectively. Packed column studies were carried out utilizing graphene magnetite as adsorbent for the removal of oil from produced water. The packed column operation was assessed using Thomas, Yan et al., Clark, Bohart and Adams and Yoon and Nelson models. Thomas model was found to best describe the column experimental data. The column was regenerated using n-Hexane and reused several times for produced water treatment with negligible decrease in its initial capacity.